Reliability Analysis of Noncoherent Systems by Logical Differential Calculus and Binary Decision Diagrams - Jozef Kostolny; Miroslav Kvassay; Stefan Kovalik (Communications - Scientific letters of the University of Zilina, 2014)
Reliability is the important characteristic of systems. Most of the systems consist of more than one component. Moreover, modern systems are very complex and they include a lot of components. Therefore, effective methods have to be developed for analysis of these systems. The techniques that have been already considered for this purpose are the Binary Decision Diagrams and the Logical Differential Calculus. However, these methods have been considered only for the coherent systems. In this paper, their use in the reliability analysis of the noncoherent systems is considered.